An analysis of EU and US productivity developments ( atotal economy and industry level perspective) - Denis, Cecile; McMorrow, Kieran; Roger, Werner; European Commission : Directorate-General for Economic and Financial Affairs (Brussels ; Belgium : European Commission: Directorate-General for Economic and Financial Affairs, 2004)
The 1990s witnessed some important shifts in the underlying growth performances of the EU and US economies, with a significant gap opening up in terms of GDP, and more importantly, GDP per capita, growth rates. From a situation over the period 1980-1995 when EU and US living standards were growing at roughly an equivalent rate, the second half of the 1990s saw the emergence of a significant growth gap in favour of the US. These EU-US differences are mirrored at the EU Member State level, with simple measures of dispersion indicating that individual country divergences relative to the average EU performance have grown by close to 50 per cent in the 1990s compared with the 1980s. These extra- and intra-EU divergences in economic fortunes have been the subject of intense research efforts in recent years, with policy makers keen to decipher the reasons for their own respective outturns and to further refine the "magic formula" for boosting their long run growth performances. The present study will contribute to this ongoing debate regarding the sources of growth in general, with specific attention being devoted to productivity determinants given their importance in shaping medium to long run changes in living standards.
Economic Papers